The effect of moderate altitude on endurance running events in the Mexico Olympics - Sucec, A. (1996)
This is a review of a paper presented at The 1996 International Pre-Olympic Scientific Congress, Dallas, TX. (Abstract 2007). The sea-level and altitude performances of 168 runners who competed in events from 800 m to the marathon were compared. Two questions were asked. 1.What was the difference of performances registered at the 1968 Olympic Games (moderate altitude 2,240 m) and best sea-level time, and 2.were the performance differences noticeable between athletes who were altitude or sea-level residents. Implications: The findings support the physiological theory that decrements in running events due to an altitude effect are dependent upon the degree to which they rely upon aerobic energy. Persons who reside at altitude perform better at altitude than non-residents despite short-term attempts at adaptation.